Ian McPhee and Elizabeth G. Pemberton. Late Classical Pottery from Ancient Corinth, Drain 1971-1 in the Forum Southwest. Corinth VII.6. pp. 400, 80 ills, 4- plates, 18 charts. 2012. Princeton NJ: American School of Classical Studies at Athens. - van der Enden, Mark (Journal of Greek Archaeology, 2020)
Volume VII.6, late Classical Pottery from Corinth, is another fine addition to the American School at Athens Corinth Excavation series. McPhee and Pemberton present in this volume the ceramic material (plus other artefacts) associated with Drain 1971-1 excavated in the southwestern area of Corinth’s Roman forum. The material attested in this deposit has been dated to the latter part of the 4th century BC and is expertly presented by the authors. Corinth VII.6, therefore, further enhances our understanding of ceramic developments at Corinth during the late Classical/early Hellenistic period, a timeframe of great geo-political change, not necessarily reflected as McPhee & Pemberton assert in the use of ceramic utensils by Corinth’s inhabitants.